Autocrine Activation of P2x7 Receptors Mediates Catecholamine Secretion in Chromaffin Cells - Acuna-Castillo, C (John Wiley and Sons Inc, 2024)
Background and Purpose: ATP is highly accumulated in secretory vesicles and secreted upon exocytosis from neurons and endocrine cells. In adrenal chromaffin granules, intraluminal ATP reaches concentrations over 100 mM. However, how these large amounts of ATP contribute to exocytosis has not been investigated. Experimental Approach: Exocytotic events in bovine and mouse adrenal chromaffin cells were measured with single cell amperometry. Cytosolic Ca2+ measurements were carried out in Fluo-4 loaded cells. Submembrane Ca2+ was examined in PC12 cells transfected with a membrane-tethered Ca2+ indicator Lck-GCaMP3. ATP release was measured using the luciferin/luciferase assay. Knockdown of P2X7 receptors was induced with short interfering RNA (siRNA). Direct Ca2+ influx through this receptor was measured using a P2X7 receptor-GCamp6 construct. Key Results: ATP induced exocytosis in chromaffin cells, whereas the ectonucleotidase apyrase reduced the release events induced by the nicotinic agonist dimethylphenylpiperazinium (DMPP), high KCl, or ionomycin. The purinergic agonist BzATP also promoted a secretory response that was dependent on extracellular Ca2+. A740003, a P2X7 receptor antagonist, abolished secretory responses of these secretagogues. Exocytosis was also diminished in chromaffin cells when P2X7 receptors were silenced using siRNAs and in cells of P2X7 receptor knockout mice. In PC12 cells, DMPP induced ATP release, triggering Ca2+ influx through P2X7 receptors. Furthermore, BzATP, DMPP, and KCl allowed the formation of submembrane Ca2+ microdomains inhibited by A740003. Conclusion and Implications: Autocrine activation of P2X7 receptors constitutes a crucial feedback system that amplifies the secretion of catecholamines in chromaffin cells by favouring submembrane Ca2+ microdomains. © 2024 British Pharmacological Society.